2003
DOI: 10.1124/jpet.103.051599
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid-Induced Desensitization of Opioid Receptor-Like 1 and μ-Opioid Receptors: Differential Intracellular Signaling Determines Receptor Sensitivity

Abstract: -Opioid receptors have been shown to contribute to orphanin FQ/nociceptin (OFQ/N)-mediated analgesia and hyperalgesia, indicating that both pro-and antinociceptive actions of OFQ/N are influenced by -opioid receptors. A 60-min activation ofor opioid receptor-like 1 (ORL1) opioid receptors natively expressed in BE(2)-C human neuroblastoma cells desensitized both -and ORL1 receptor-mediated inhibition of cAMP accumulation. The mechanism(s) of OFQ/N-mediated -and ORL1 cross talk involves the conventional protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Moreover, PKC inhibitor and PKG inhibitor had no effects on isoproterenol-induced H1R phosphorylation, suggesting that neither PKC nor PKG is involved in heterologous H1R phosphorylation induced by b2R activation. Involvement of GRKs in heterologous receptor phosphorylation has been demonstrated (21). This report demonstrated that m -opioid receptor stimulation with its agonist led to translocate the GRKs to the membrane, and these kinases are involved in the other Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, PKC inhibitor and PKG inhibitor had no effects on isoproterenol-induced H1R phosphorylation, suggesting that neither PKC nor PKG is involved in heterologous H1R phosphorylation induced by b2R activation. Involvement of GRKs in heterologous receptor phosphorylation has been demonstrated (21). This report demonstrated that m -opioid receptor stimulation with its agonist led to translocate the GRKs to the membrane, and these kinases are involved in the other Fig.…”
Section: Discussionmentioning
confidence: 77%
“…A 1 hour treatment of BE(2)-C human neuroblastoma cells with the mu agonist DAMGO reduced N/OFQ-mediated inhibition of cAMP accumulation. Although the same treatment of SH-SY5Y cells was ineffective in reducing N/OFQ signaling (Mandyam et al, 2000(Mandyam et al, , 2003. Likewise, in CHO or HEK 293 overexpressing recombinant NOP and mu receptors, mu receptor activation had no effect on NOP receptor-mediated stimulation of ERK1/2 (Hawes et al, 1998) or inhibition of cAMP .…”
Section: Cross Talk With Mu Opioid Receptorsmentioning
confidence: 94%
“…To test the roles of GRK2 and GRK3 in OFQ/N-induced receptor desensitization in Flag-BE cells, we used GRK isoform-specific antisense DNA treatment, which we reported previously selectively reduces levels of GRK2 or GRK3 Mandyam et al, 2003). OFQ/ N-induced receptor desensitization was attenuated in cells pretreated with GRK2 antisense but not GRK2 sense DNA (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The role of GRK2 in OFQ/N-mediated increase in receptor phosphorylation in Flag-BE cells was tested by depleting GRK2 levels with GRK2 antisense DNA treatment, as described previously (Aiyar et al, 2000;Thakker and Standifer, 2002;Mandyam et al, 2003). This GRK2 antisense DNA treatment reduced GRK2 levels more than 50% (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation